Naturalism, Wittgensteinian Grammar, and Initiation into Interreligious Exploration - Kiem, Youngjin ca. 20./21. Jh. (Neue Zeitschrift für systematische Theologie und Religionsphilosophie, 2021)
This paper lays out the first step towards a complete methodology of interreligious investigation, emphasizing the issue of how we should treat individual religions while not committing ourselves to religious apologetics in general. From that perspective, I introduce two theoretical requirements that the methodology of interreligious exploration should fulfill, what we call the constraint of consistency and ontology and the constraint of absoluteness and plurality. The article expounds how and on what grounds those two methodological constraints can be fulfilled by the philosophical notions of "naturalism" and "religion as grammar." In doing so we reach the following methodological canons: When initiating interreligious exploration, (1) adopt an "open-ended minimal naturalism" in which transcendent realities appearing in individual religions are neither affirmed nor denied in advance, and (2) on the basis of that naturalism, take individual religions as different systems of grammar, that is, distinct linguistic-conceptual frameworks upon which one can see and understand various religious worlds in a constitutive way. The paper is the exposition and defense of these ideas.